FUZZY TSUKAMOTO METHOD IN DETERMINING CORN QUALITY FOR ANIMAL FEED - Dinur Syahputra; M. Rhifky Wayahdi; Subhan Hafiz Nanda Ginting (INFOKUM, 2020)
Animal feed is the largest cost component in the livestock industry. The existence of a solution to reduce the percentage of feed costs can have a tremendous positive impact for farmers. Animal feed is generally obtained by buying factory-produced animal feed that tends to be expensive or by making their own animal feed. However not all breeders can make their own animal feed because to make good feed the formulation process is. Fuzzy Tsukamoto is one of the fuzzy logic in which the methodology of the problem solving control system is suitable to be implemented on the system